Calibration of X-ray space telescopes - Shchagin, A.V.; Sanin, V.M.; Sotnikov, V.V.; Voronko, V.A. (Вопросы атомной науки и техники, 2004)
In this work the new concept of a source of X-ray beam for ground calibration of next-generation telescopes is
proposed. This facility contains a source of a parametric X-ray radiation (PXR). The source would provide a
monochromatic X-ray beam and would allow smooth tuning of photon energy and linear polarization direction. The
facility is intended for calibration of registration efficiency, polarization sensitivity and angular properties of space
telescopes and other X-ray and soft gamma-ray instruments in the energy range of incident photons from several
keV up to hundreds keV. Запропонована нова концепція джерела рентгенівського пучка для наземного калібрування телескопів
наступного покоління. Цей пристрій містить джерело параметричного рентгенівського випромінювання
(ПРВ). Джерело забезпечує монохроматичний рентгенівський пучок і плавну перебудову енергії фотона і
напрямку лінійної поляризації. Пристрій призначений для калібрування ефективності реєстрації, чутливості
до поляризації і кутових властивостей космічних телескопів і інших рентгенівські і м'які гамма-
випромінювання приладів в енергетичному діапазоні падаючих фотонів від кількох до сотень кеВ. Предложена новая концепция источника рентгеновского пучка для наземной калибровки телескопов следующего поколения. Это устройство содержит источник параметрического рентгеновского излучения
(ПРИ). Источник обеспечивает монохроматический рентгеновский пучок и плавную перестройку энергии
фотона и направления линейной поляризации. Устройство предназначено для калибровки эффективности
регистрации, чувствительности к поляризации и угловых свойств космических телескопов и других рентгеновских и мягкого гамма-излучения приборов в энергетическом диапазоне падающих фотонов от нескольких до сотен кэВ.